2006
DOI: 10.1109/tpami.2006.141
|View full text |Cite
|
Sign up to set email alerts
|

Full-frame video stabilization with motion inpainting

Abstract: Video stabilization is an important video enhancement technology which aims at removing annoying shaky motion from videos. We propose a practical and robust approach of video stabilization that produces full-frame stabilized videos with good visual quality. While most previous methods end up with producing smaller size stabilized videos, our completion method can produce full-frame videos by naturally filling in missing image parts by locally aligning image data of neighboring frames. To achieve this, motion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
344
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 493 publications
(350 citation statements)
references
References 31 publications
2
344
0
4
Order By: Relevance
“…In [Gleicher and Liu 2008] the stabilized camera motion is computed by interpolating between homography transformations using matrix logarithms. Matsushita et al [2006] discuss additional important aspects of video stabilization, such as extending the stabilized frames to become full-frames and reducing the motion blur.…”
Section: Introductionmentioning
confidence: 99%
“…In [Gleicher and Liu 2008] the stabilized camera motion is computed by interpolating between homography transformations using matrix logarithms. Matsushita et al [2006] discuss additional important aspects of video stabilization, such as extending the stabilized frames to become full-frames and reducing the motion blur.…”
Section: Introductionmentioning
confidence: 99%
“…Xiang et al [22] showed how to utilize the video retargeting method to improve the composition of video contents. Temporal information [23] and camera stability [24] were also considered to improve video aesthetic quality. More recently, Lu et al proposed a spatio-temporally consistent color and structure optimization method [25].…”
Section: Related Workmentioning
confidence: 99%
“…Motion denoising has been addressed before in a global manner, known as video stabilization (e.g. [11,10]). Camera jitter (mostly from hand-held devices) is modeled using image-level transforms between consecutive frames, which are used to synthesize a sequence with smoother camera motion.…”
Section: Background and Related Workmentioning
confidence: 99%